Knockdown of a laccase in Populus deltoides confers altered cell wall chemistry and increased sugar release. Issue 10 (15th April 2016) - Bryan, Anthony C.; Jawdy, Sara; Gunter, Lee; Gjersing, Erica; Sykes, Robert; Hinchee, Maud A. W.; Winkeler, Kimberly A.; Collins, Cassandra M.; Engle, Nancy; Tschaplinski, Timothy J.; Yang, Xiaohan; Tuskan, Gerald A.; et al.
Summary: Plant laccases are thought to function in the oxidation of monolignols which leads to higher order lignin formation. Only a hand‐full of laccases in plants have been functionally evaluated, and as such little is known about the breadth of their impact on cell wall chemistry or structure. Here, we describe a previously uncharacterized laccase from Populus, encoded by locus Potri.008G064000, whose reduced expression resulted in transgenic Populus trees with changes in syringyl/guaiacyl ratios as well as altered sugar release phenotypes. These phenotypes are consistent with plant biomass exhibiting reduced recalcitrance. Interestingly, the transgene effect on recalcitrance is dependent on a mild pretreatment prior to chemical extraction of sugars. Metabolite profiling suggests the transgene modulates phenolics that are associated with the cell wall structure. We propose that this particular laccase has a range of functions related to oxidation of phenolics and conjugation of flavonoids that interact with lignin in the cell wall.